2018
DOI: 10.1016/j.applanim.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing changes in activity and feeding behaviour of lactating dairy cows during behavioural and silent oestrus

Abstract: The normal time budgets of dairy cows are influenced by oestrus, with cows spending less time resting and eating but more time walking. Previous studies have shown that cows spend approximately 21% less time feeding where the day of oestrus is assumed to be the day of successful artificial insemination. The objective of the present study was to determine whether the number of steps, lying time, lying bouts, dry matter intake (DMI), feeding duration and the number of visits to feed were affected by behavioural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
5
16
1
1
Order By: Relevance
“…In another study conducted in cattle (Bos taurus), Kumar and Archunan (2006) analysed FA in urine, and reported that lauric, tridecanoic, myristic and stearic were present in pro-oestrus, oestrus and dioestrus samples but were not different in concentration. Although Megalac is a source of C16:0 and C18:1n9c FA (Scollan et al, 2001), and dry matter intake has been previously shown to be reduced during oestrus (Zebari et al, 2018) C16:0 and C18:1n9c FA concentrations were similar during oestrus and day 14 of dioestrus in the present study.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In another study conducted in cattle (Bos taurus), Kumar and Archunan (2006) analysed FA in urine, and reported that lauric, tridecanoic, myristic and stearic were present in pro-oestrus, oestrus and dioestrus samples but were not different in concentration. Although Megalac is a source of C16:0 and C18:1n9c FA (Scollan et al, 2001), and dry matter intake has been previously shown to be reduced during oestrus (Zebari et al, 2018) C16:0 and C18:1n9c FA concentrations were similar during oestrus and day 14 of dioestrus in the present study.…”
Section: Discussioncontrasting
confidence: 58%
“…Standing oestrous behaviour is detected in only 50% of oestrous cows (Lyimo et al, 2000). Furthermore, it has been reported (Palmer et al, 2010;Zebari et al, 2018) that only 50% to 60% of cows express behavioural signs of oestrus, with the remaining 40% to 50% having ovulations without expression of behavioural oestrus which obviously cannot be detected by observation or automated methods of oestrous detection.…”
Section: Introductionmentioning
confidence: 99%
“…error rate = number of false positives number of true positives + number of false positives (2) precision = number of true positives number of true positives + number of false positives (3) where the number of true positives was achieved by counting the number of times that the cow was correctly located by the system, the number of false positives was obtained by computing the number of times that the cow was wrongly positioned by the system. The planimetric location error within the acceptable range (mean location error − 1.96 × standard deviation, mean location error + 1.96 × standard deviation) was considered as a correct positioning, and vice versa.…”
Section: Positioning Performance Of the Neck Tagmentioning
confidence: 99%
“…Other signs of estrus include mounting of other cows, increased activity, and mucous discharge from the vulva. While standing to be mounted is recognized as the primary behavioral sign of estrus, other behaviors, such as anogenital sniffing, restlessness, bellowing, chin resting, head mounting, and an attempt to mount are considered secondary symptoms [3]. Progesterone measurement in plasma or milk can aid detection of estrus by determining error in other detection methods, such as false positives when using activity [4].…”
Section: Introductionmentioning
confidence: 99%
“…With Foraging, Lying, Standing and Walking, four types of behaviour could be found in the GPS data by training classification and regression trees on the pattern of the characteristic movement metrics of these behaviours. Valuable insights could be gathered from hard data concerning the distances an animal has walked per day or the speed with which an animal moves about potential lameness [ 21 ] or with regard to oestrus detection [ 3 , 22 ]. Important work has been carried out on the walked distances of feral horses, stating averaged distances varying from 3.5 km per day [ 23 ] to 9 km per day [ 24 ] to 15.9 km per day [ 25 ].…”
Section: Introductionmentioning
confidence: 99%